The username can contain only lower-case alphanumeric characters, underscores, and hyphens, and must begin and end with an alphanumeric character.: Analisis Manajemen Risiko Operasional pada Layanan Mobile Banking Bank Syariah Indonesia Pasca Gangguan Sistem Tahun 2024 - Fitria Asas; Izzatul Ilmiyah; Monica Resavita (Universitas Bojonegoro, 2026)
Banking services have shifted toward mobile banking systems with the development of digital technology. While service digitization can improve accessibility, it also increases exposure to operational risks resulting from system failures, process errors, and cybersecurity attacks. This study employed a descriptive quantitative method with a sample of 100 BSI Mobile customers selected using a purposive sampling technique. Data analysis was conducted using descriptive statistics in the form of means, percentages, and frequency distributions. The results showed that the operational risk level was in the high category with an average score of 3.68. The risk identification indicator scored 3.82, risk assessment 3.75, risk mitigation 3.60, and risk monitoring 3.55. The results indicated that system disruptions resulted in transaction delays, decreased customer satisfaction, and potentially impacted the bank's reputation. Therefore, strengthening information technology infrastructure, increasing system capacity, and optimizing operational risk management on an ongoing basis is necessary.